2012
DOI: 10.5923/j.economics.20120201.04
|View full text |Cite
|
Sign up to set email alerts
|

Concept, Measurement and Causes of Poverty: Nigeria in Perspective

Abstract: The paper discusses the concept of poverty and elucidates the various methods of measurement used in evaluating poverty. Causes of poverty in Nigeria were also brought into perspective. It was concluded that inadequate economic growth is the main cause of poverty in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 23 publications
0
13
1
1
Order By: Relevance
“…However, the study concludes that income inequality is a great determinant of poverty. Olowa (2012) examined the measurements and causes of poverty in Nigeria. The review identified the causes of poverty to include low economic growth, unemployment, low productivity and wages in the informal sector, inappropriate macroeconomic policies, economic degradation, crime and violence, workers' retrenchment among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the study concludes that income inequality is a great determinant of poverty. Olowa (2012) examined the measurements and causes of poverty in Nigeria. The review identified the causes of poverty to include low economic growth, unemployment, low productivity and wages in the informal sector, inappropriate macroeconomic policies, economic degradation, crime and violence, workers' retrenchment among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nigeria is mainly characterised by rural settlement with high poverty index (Olowa, 2012). To this effect, agricultural activity remains the major occupation of the people.…”
Section: Introductionmentioning
confidence: 99%
“…The less privileged who wish to be economically active engage in small scale businesses. Poverty is the lack of access to basic needs such as proper nutrition, housing, water, healthcare, access to productive resources, education, work skills, tools, and political and civil rights to participate in decisions concerning their socio-economic conditions (Olatomide, 2012).…”
Section: Significance To Social Changementioning
confidence: 99%